Periodontal flap closure using a simplified autologous fibrin glue preparation: A report of two successful cases - Bhumit Pradipbhai Dave; Sunil Sathyanarayana (Wolters Kluwer Medknow Publications, 2020)
Although suturing is an integral part of periodontal flap surgery, it has disadvantages such as difficulty in plaque control, increased postoperative discomfort, and higher infection rate. To overcome these problems, a search for alternatives and possibly a sutureless technique has continued. Fibrin glue is one such biological tissue adhesive, mimicking the final stages of coagulation with several advantages. This report shows the use of an autologous fibrin glue in two cases, prepared using a simplified method. At the end of periodontal flap surgery, the flaps were closed with sutures in two papillae and fibrin glue in other two papillae in both cases. The papillae closed with fibrin glue showed better healing and good stability after flap closure. This simplified preparation of autologous fibrin glue has not been reported till date as found from literature search.